Do "pai" ao "irmão", representações familiares em transição : a experiência de uma empresa capixaba de refrigerantes - Waiandt, Claudiani (2005)
This dissertation investigates the family and its social representations in the construction of the daily practices of administration in a company of drinks in the State of Espirito Santo. Considering the proposal, the central objective is to investigate,